“Catalisadores Au/m-ZrO2 aplicados na conversão direta do etanol em acetato de etila: efeito do grau de recobrimento do suporte nas propriedades catalíticas” - Ribeiro, Murillo Cardoso (2018)
In this present work, the direct formation of ethyl acetate from ethanol was studied using monometallic catalysts of Au supported on m-ZrO2. Other supports, such as MgO and SiO2, as well as Cu-based catalysts were prepared for comparison. Au-based catalysts were prepared by deposition-precipitation method with NaOH and investigated by different characterization methods, such as X-ray diffraction (XRD), N2 physisorption, X-ray excited photoelectron spectroscopy (XPS), X-ray spectroscopy Diffuse reflectance in the infrared region with adsorbed CO Fourier transform (DRIFTS-CO), inductively coupled plasma optical emission spectroscopy (ICP-OES), extended X-ray absorption fine structure spectroscopy (EXAFS), and electron microscopy of transmission (TEM). The gold loading was confirmed by ICP-OES and it showed a close correlaction with the synthesis pH, as well as with the chemical composition of the support. For all the analyzed catalysts, no reflection corresponding to Au could be observed by XRD. In addition, Au NPS presented as small crystallites and highly dispersed on the surface of the support. The average size of Au NPS, determined by TEM, was dependent on the chemical composition of the support, the synthesis pH and the activation temperature of the catalysts. Analysis of EXAFS data showed only Au-Au binding distance, indicating that Au0 prevails in reaction condition. The catalytic tests revealed, for the first time, high selectivity to ethyl acetate using Au-based catalysts, whose value (yield higher than 63.0%) for the Au / m-ZrO2 catalyst, with a real Au content of 5,01%, was higher than that achieved by the classical Cu-based catalysts. In addition, the results presented in this thesis have allowed to propose that not only the extension of the metal-support interface, but also the degree of coverage of ZrO2 by Au, as well as the electronic properties of this metal are fundamental factors for the high performance presented by these catalysts in the direct transformation of ethanol into ethyl acetate.